Gambaran Perilaku Anak Berkebutuhan Khusus dan Penanganannya oleh Guru di Sekolah Dasar Inklusi Kabupaten Sleman - Galih Adi Pratama; Ibrahim Rahmat; Sri Warsini (Jurnal Keperawatan Klinis dan Komunitas (Clinical and Community Nursing Journal), 2019)
Background: Sleman District Government through the Child Friendly City (Kota Layak Anak/KLA) has a child-friendly school program in the form of inclusive school. The implementation of inclusive education in Indonesia has not met the current standard. There has been no further study regarding the behavior of children with special needs in inclusive schools and how teacher handle their behaviors in Sleman. Therefore, research on the experience of classroom teachers in finding and handling behavior of children with special needs in inclusive primary school of Sleman Regency is important.Objective: To describe the experience of classroom teachers in finding and handling behavior of children with special needs in inclusive primary school Sleman Regency.Method: This research was qualitative with phenomenology approach. The subjects were six class teachers, six parents/guardians, and two education-office civil servants whom were selected by purposive sampling method. Data obtained from the results of in-depth interviews were processed using content analysis.Result: Children with special needs had several behavioral problems, i.e: internalizing problems in the form of anxiety, somatic disorder, and withdrawal; externalizing issues (behavior) in the form of aggressive behavior, and destructive behavior; other behavioral problems such as attention disorder, thought problem, and social problem. The handling of children with special needs at school was based on the strategy of the school and its classroom teacher.Conclusion: There are five themes in this research that are internalizing (emotion) children with special needs, externalizing (behavioral) problem of children with special needs, other behavior problem, classroom teacher strategy in handling children with special needs behavior, and school strategy in handling children with special needs behavior.ABSTRAKLatar belakang: Pemerintah Kabupaten Sleman melalui program Kota Layak Anak (KLA) mempunyai program sekolah ramah anak yang diimplementasikan dalam sekolah inklusi. Pelaksanaan pendidikan inklusi di Indonesia masih belum memenuhi standar yang ada. Belum ada kajian lebih lanjut mengenai sekolah inklusi di Kabupaten Sleman khususnya mengenai perilaku Anak Berkebutuhan Khusus (ABK) di sekolah inklusi dan bagaimana penanganan perilaku yang telah dilakukan guru di sekolah. Oleh karena itu, penelitian tentang pengalaman guru kelas dalam menemukan perilaku pada anak berkebutuhan khusus dan penanganannya di sekolah dasar inklusi Kabupaten Sleman, penting untuk dilakukan.Tujuan: Mengetahui pengalaman guru kelas dalam menemukan perilaku pada anak berkebutuhan khusus dan penanganannya di sekolah dasar inklusi Kabupaten Sleman.Metode: Jenis penelitian ini adalah kualitatif, menggunakan pendekatan fenomenologi. Subjek penelitian adalah 6 guru kelas, 6 orang tua/wali, dan 2 pegawai dinas yang dipilih dengan purposive sampling. Data diperoleh dari hasil wawancara mendalam. Data dianalisis menggunakan analisis konten.Hasil: ABK mempunyai beberapa masalah perilaku, yaitu masalah internalizing (emosi) yang meliputi kecemasan, gangguan somatis, dan menarik diri; masalah externalizing (perilaku) yang meliputi perilaku agresif dan perilaku merusak; serta masalah perilaku lainnya, seperti gangguan perhatian, masalah pemikiran, dan masalah sosial. Penanganan ABK di sekolah dilakukan berdasarkan strategi dari sekolah dan yang dilakukan oleh guru kelas.Kesimpulan: Terdapat lima tema dalam penelitian ini, yaitu masalah internalizing (emosi) ABK, masalah externalizing (perilaku) ABK, masalah perilaku lainnya, strategi guru kelas dalam penanganan perilaku ABK, dan strategi sekolah dalam penanganan perilaku ABK.